Upaya Peningkatan Pemahaman Huruf Hijaiyah Melalui Media Genius Card di SMP Qur’ani - Isnin Marlina; Siti Fatimah; Imam Subarkah (Tarbi: Jurnal Ilmiah Mahasiswa, 2023)
This study aims to improve understanding of hijaiyah letters by using genius card media. This study used Classroom Action Research (CAR) at Qur'ani Middle School which was conducted in April-May 2023 with 20 class VII students as research subjects. Data analysis techniques using observation. The results of this study indicate that there is an increase in each cycle. The research consisted of two cycles with four main activities in each cycle, namely planning, action, observation and reflection. Observations were made directly to see the application of the media genius card program. The results of the analysis showed an increase, namely in the first cycle there were 40% of students getting a complete score increased in cycle II there were 90% of students getting a complete score in understanding hijaiyah letters using genius card media. So it can be concluded that genius card media can improve understanding of hijaiyah letters